2024
DOI: 10.3390/antiox13010086
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor and Oxidative Stress in Tendon Degeneration: A Molecular Perspective

Hamzah Shahid,
Vivek Kumar Morya,
Ji-Ung Oh
et al.

Abstract: Tendinopathy is a debilitating condition marked by degenerative changes in the tendons. Its complex pathophysiology involves intrinsic, extrinsic, and physiological factors. While its intrinsic and extrinsic factors have been extensively studied, the role of physiological factors, such as hypoxia and oxidative stress, remains largely unexplored. This review article delves into the contribution of hypoxia-associated genes and oxidative-stress-related factors to tendon degeneration, offering insights into potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 163 publications
0
1
0
Order By: Relevance
“…However, the primary function of this isoform remains unclear. Both HIF-1α and HIF-2α contribute to tumor hypoxia, but HIF-1α appears to be more prominently involved in energy metabolism and angiogenesis [ 18 , 19 ]. Many studies have suggested that HIF-1α is a key regulator of many essential pathways, including those of growth factors, glycolytic enzymes, the modulation of natural killer cells, resistance to chemotherapy and radiotherapy, and the promotion of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the primary function of this isoform remains unclear. Both HIF-1α and HIF-2α contribute to tumor hypoxia, but HIF-1α appears to be more prominently involved in energy metabolism and angiogenesis [ 18 , 19 ]. Many studies have suggested that HIF-1α is a key regulator of many essential pathways, including those of growth factors, glycolytic enzymes, the modulation of natural killer cells, resistance to chemotherapy and radiotherapy, and the promotion of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%